An advanced quadcopter with Pid controller using both Gyroscopes and Accelerometers - Tran , Thu Ha; Nguyen , Van Thai; Le , Hoang Minh; Duong , Thi Cam Tu (Journal of Technical Education Science, 2016)
This project focus on design a quadcopter and development an algorithm so that help it can navigate and self-balance in both indoor and outdoor enviroment, which can be used as a framework for applications such as data collection, ground surveillance, etc. The proposed algorithm allows the quadcopter can fly from its current location to the given location in space. Assuming that there are obstacles in front of the quadcopter, it has to recognize and avoid these obstacles. The developed quadcopter consists of four rotors mounted on four brushless motors to allow lifting and propelling the quadcopter. Arduino platform was used for programming. There are two PID controllers have been applied to control the quadcopter's self-balance and obstacle avoidance. The PID1 uses input values from an IMU sensor which returns values regarding angles and angular velocities of the quadcopter's frame and a GPS module to control the self-balance of the quadcopter. The PID2 uses input values from 5 ultrasonic sensors, four sensors are mounted around and the fifth is mounted under bottom of the quadcopter's frame to control the obstacle avoidance.